ANALISYS OF PROCESS PERFORMANCE MEASUREMENT MODELS - Simeunović, Barbara P; Slović, Dragoslav R; Radaković, Jelena Andreja N (International Journal of Economic Practice and Policy, 2016)
In the literature, there are number of models that provide guidelines for the performance measurement system development and examine performance measurement problems from different perspectives. In this paper, some of the most important performance measurement models are considered. Furthermore, comparative analysis of these models, according to 11 criteria, was done. It was noticed that the majority of models takes into account the strategy or goals while determining performance but most of them don’t specify performance indicators and only give an indication for their determination. Also, none of models link directly organizational goals and proces performance indicators, which would allow model flexibility and adaptibility. On this basis, the need to develop a new model that would overcome these shortcomings was identified, and this represents a direction for further research.
Keywords: process performance measurement models; PROCESS PERFORMANCE MEASUREMENT; goals; processes; process performance indicators; ANALISYS; criteria